Myostatin Gene Expression and Its Application on Goat Breeding Programme - Aron Batubara (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2017)
Characteristics of double muscled growth in animals are influenced by myostatin gene (MSTN). Myostatin gene is known as a member of the growth gene's superfamily (TGF-β) which works to suppress the muscle growth. However, the presence of six mutations on MSTN cause the gene inactive, and trigger the occurrence of muscle hypertrophy. Identification of myostatin gene was conducted by molecular techniques, and the most common method is polymerase chain reaction followed by single-strand conformation polymorphism (PCR-SSCP). Research on sheep and goat in several countries showed that there had been several variations occurred in myostatin gene but further studies are required to correlate these variations to body weight gain and other important production parameters. For goat production in Indonesia, myostatin mutations cause double muscling that can be utilised for genetic improvement in goat breeding plan to produce a new breed with high quality meat.